2016
DOI: 10.1016/j.mehy.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Early-life stress and reproductive cost: A two-hit developmental model of accelerated aging?

Abstract: a b s t r a c tTwo seemingly independent bodies of research suggest a two-hit model of accelerated aging, one highlighting early-life stress and the other reproduction. The first, informed by developmental models of earlylife stress, highlights reduced longevity effects of early adversity on telomere erosion, whereas the second, informed by evolutionary theories of aging, highlights such effects with regard to reproductive cost (in females). The fact that both early-life adversity and reproductive effort are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 128 publications
(150 reference statements)
2
27
0
Order By: Relevance
“…Several different lines of research have found links between adverse life experiences in the early years of life and adult telomere length (1113). These studies are difficult to interpret given that adversities tend to co-occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different lines of research have found links between adverse life experiences in the early years of life and adult telomere length (1113). These studies are difficult to interpret given that adversities tend to co-occur.…”
Section: Discussionmentioning
confidence: 99%
“…For example, perceived neighborhood quality (46), anxiety (7), exposure to intimate partner violence (8, 9), and being the primary caregiver of a child with a chronic condition (10) are all inversely correlated with telomere length, as typically measured during adulthood. Associations between telomere length and adverse early life experiences have also been observed (1113). Adults reporting physical or emotional neglect during childhood had shorter telomeres than their counterparts who did not report any childhood maltreatment (14).…”
Section: Introductionmentioning
confidence: 95%
“…It should be noted that DNA repair mechanisms and telomere length are mechanistically related (55), and telomere length can be affected by many elements, such as telomerase activity, oxidative stress, antioxidant activity, inflammation, the hypothalamus-pituitary-adrenal axis (glucocorticoid levels), and mitochondria regulation (56). One study found that among non-Hispanic white women, one standard deviation in longer leukocyte telomere length was associated with a 0.43 year later age at menopause (57).…”
Section: Menopausementioning
confidence: 99%
“…Most companies have made the switch over to synthesizing these colors from petroleum, but consumers have no way of knowing how the dye used in the cosmetics was synthesized, and using petroleum has its own hazards (See Petrolatum ). ** Another major concern of ethanolamine compounds is their ability to react with nitrites and form carcinogenic nitrosamines (21, 56). Nitrites can come from degradation of some cosmetic preservatives when they are exposed to air (57) and nitrites are sometimes used in cosmetics as anti-corrosive ingredients (58).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation